Similarities and differences in two works of Ivan Bunin (The Village) and Faris Zarzour (The Sinners) (A Comparative study) - محمود, عيد; محمود , دلال سليمان (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This study deals with revealing the points of similarity and difference between two literary works, Russian and Syrian, by writers Ivan Bunin and Faris Zarzour. who presented two works that refer to a period of time full of turmoil, which left a clear mark on literature in general, and the novel in particular, as the topics that occupied the minds of writers converged, including (Bunin) and (Zarzour), The village and the problems of life in it were the most present in literature at the time. The writers dealt with social issues within their class-divided societies, and they depicted human suffering under those circumstances. Various ideological conflicts were also reflected in these works. The writers presented ideas that touched life, touching on the human view of the universe and the reality and purpose of existence. Their works were characterized by realism, because it is the approach closest to writers to express the issues of their societies, as well as the convergence of artistic methods through which writers presented their greatest literary productions.